2021
DOI: 10.1038/s41598-021-87429-y
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of surface pattern and contour shape in the tilt after effects evoked by symmetry

Abstract: Integration of multiple properties of an object is a fundamental function of the visual cortex in object recognition. For instance, surface patterns and contour shapes are thought to be crucial characteristics that jointly contribute to recognition. However, the mechanisms of integration and corresponding cortical representations have not been fully clarified. We investigated the integration of surfaces and shapes by examining the tilt after effects (TAEs) evoked by the symmetry of patterns and contours. As sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
1
1
Order By: Relevance
“…Although a substantial number of natural objects are symmetric and the solid perceptual representation of symmetry has been reported ( Sharman and Gheorghiu, 2018 ; Sakai et al, 2021 ), only a fraction of V4 neurons showed significant tuning to symmetry in the present experiment. The limited spatial extent of the receptive filed might account for this discrepancy.…”
Section: Discussioncontrasting
confidence: 57%
“…Although a substantial number of natural objects are symmetric and the solid perceptual representation of symmetry has been reported ( Sharman and Gheorghiu, 2018 ; Sakai et al, 2021 ), only a fraction of V4 neurons showed significant tuning to symmetry in the present experiment. The limited spatial extent of the receptive filed might account for this discrepancy.…”
Section: Discussioncontrasting
confidence: 57%
“…For instance, contour shapes and high-contrast textures are good candidates to examine the relevance to neural responses. The integration and interaction of contour shapes and surface textures are also crucial in the examination [ 50 ]. It is also important to investigate the interactions with depth cues.…”
Section: Discussionmentioning
confidence: 99%